Author Correction: Regulation of microRNA biogenesis and its crosstalk with other cellular pathways. Issue 12 (December 2018) - Treiber, Thomas; Treiber, Nora; Meister, Gunter
In Figure 1b, the GHG sequence motif in the primary microRNA has been moved to the basal stem and the ruler of the basal stem has been shortened to more precisely delineate 11 base pairs. The changes have been made in the HTML and PDF versions of the manuscript.